The Big ‘I’, Little ‘I’ Technique: A Case Study of Cognitive Behavioural Therapy Intervention on Self-Acceptance among Young Drug Addicts - Huzili Hussin; Alyaa Insyirah Huzili; Nurul Mazidah Sainani; Saralah Devi Mariamdaran Chethiyar, (Journal of Human Development and Communication (JoHDeC), 2025)
This case study aimed to explore the feelings of the residents in one of the care and cure rehabilitation centre in North Malaysia. The outcome from this study will help them increase the ownership of their own feelings and decision. This study leads to further findings their thoughts living as young drug addicts. An intervention session was conducted for about three hours involving eight participants and two facilitators . The intervention session was conducted using artwork as a medium for exploration and Cognitive Behavioural Therapy as the intervention technique. These two elements helped explore the clients’ emotions and thoughts deeply through verbal and non-verbal communication. Apart from that, the interventions used helped the clients on decision-making and achieve self-acceptance.